Analisis Kinerja Keuangan Koperasi Unit Desa (KUD) Ulun Tanjung, Desa Kerobokan, Kabupaten Badung, Bali - DAMAYANTI, YOVITA; WIDHIANTHINI, WIDHIANTHINI; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.2, Desember 2022DO - 10.24843/JAA.2022.v11.i02.p40, 2022)
The Financial Performance Analysis of Rural Cooperative of Ulun Tanjung,  in Kerobokan, District Badung Regency, Bali Financial performance analysis was carried out to determine the financial performance of KUD Ulun Tanjung. The research objective was determine financial performance of KUD Ulun Tanjung in terms of liquidity, solvency, activity, and profitability ratio, as well as to analyze the development of balance sheets and income statements in terms of trend and common size analysis. Data processed of the research were sourced from secondary data, financial statements of KUD Ulun Tanjung in 2017-2021 and also literature related to this research. The types of data used in this research are qualitative and quantitative data. Data collection is done by documentation, interviews, and literature study. Data analysis used ratio analysis, trend analysis, and common size. The results of the research show that the financial performance of KUD Ulun Tanjung is in a condition that tends to decline during the Covid-19 pandemic. The trend analysis of KUD Ulun Tanjung tends to experience a declining percentage during the Covid-19 pandemic. The common size also experiences a percentage that tends to decrease during the Covid-19 pandemic. Therefore, KUD Ulun Tanjung needs to reduce the amount of debt and receivables and maximize its own capital, income, and use of assets to stabilize its financial performance.